These strange ashes - Elliot, Elisabeth (Harper & Row, 1979)
These Strange Ashes tells the story of a group of women missionaries among the Colorado Indians of Ecuador, facing the challenge of bringing the Gospel to an aloof people without written language, living scattered throughout the dark forests. --From publisher's description